From Social Media to Checkout: The FoMO Phenomenon in Indonesia's Beauty Sector - Ida Ayu Santhi Adnyani Dewi; Ida Ayu Oka Martini (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
The skincare market in Indonesia is experiencing rapid growth, driven by the increasing young population. This research examined the impact of brand image, viral marketing, and influencer marketing on consumer purchasing decisions, with Fear of Missing Out (FoMO) as a mediating factor. A quantitative approach is employed, utilizing a non-probability sampling method, specifically incidental sampling. The sample consists of 220 consumers in Indonesia who have purchased and used Skintific skincare products. Data was collected through an online questionnaire. The analysis was conducted using descriptive analysis with SPSS and inferential analysis through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicated that brand image and viral marketing did not significantly affect purchasing decisions, but influencer marketing had a positive and significant effect. In contrast, FoMO had a positive and significant effect on purchasing decisions. Additionally, brand image, viral marketing, and influencer marketing positively and significantly influenced FoMO. FoMO is a mediating variable that strengthens the impact of brand image, viral marketing, and influencer marketing on purchasing decisions. These findings suggested that, in marketing strategies, fostering FoMO through various campaigns can be a more effective approach to driving consumer purchasing decisions. These findings contribute to the company by optimizing the impact of FoMO on Skintific through strategies such as launching limited-edition products, offering time-limited deals, and utilizing real-time user reviews to encourage consumers to make quicker purchase decisions.